2017
DOI: 10.1007/s10126-017-9768-2
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the First High-Density Genetic Linkage Map and Analysis of Quantitative Trait Loci for Growth-Related Traits in Sinonovacula constricta

Abstract: The razor clam (Sinonovacula constricta) is an important aquaculture species, for which a high-density genetic linkage map would play an important role in marker-assisted selection (MAS). In this study, we constructed a high-density genetic map and detected quantitative trait loci (QTLs) for Sinonovacula constricta with an F cross population by using the specific locus amplified fragment sequencing (SLAF-seq) method. A total of 315,553 SLAF markers out of 467.71 Mreads were developed. The final linkage map was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Several studies, however, indicated that the presence of segregation distortion markers made little effect on the applications of linkage maps for further analysis such as QTL mapping (Zhang et al, 2010). In addition, the distorted markers for linkage map construction could improve both the genome coverage of the genetic map and the identification of linked QTLs, and filtering out all the distorted markers may lead to a massive loss of genetic information and the decrease of genome coverage (Niu et al, 2017). To increase the genome coverage of the final genetic map, 181 markers that showed significant segregation distortion (χ2, p < 0.05) were retained and assigned to 15 LGs in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, however, indicated that the presence of segregation distortion markers made little effect on the applications of linkage maps for further analysis such as QTL mapping (Zhang et al, 2010). In addition, the distorted markers for linkage map construction could improve both the genome coverage of the genetic map and the identification of linked QTLs, and filtering out all the distorted markers may lead to a massive loss of genetic information and the decrease of genome coverage (Niu et al, 2017). To increase the genome coverage of the final genetic map, 181 markers that showed significant segregation distortion (χ2, p < 0.05) were retained and assigned to 15 LGs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other genotyping strategies, it has several advantages and characteristics: (i) ensure the genotyping accuracy by deep sequencing, (ii) reduce the sequencing costs by RRL strategy, (iii) optimize the marker efficiency by pre-designed RRL strategy scheme, and (iv) employ the double barcode system for large populations (Sun et al, 2013). SLAF-seq has been used for high-density genetic map construction in an increasing number of aquatic animals up to now, such as common carp (Sun et al, 2013), Pacific white shrimp (Yu et al, 2015), freshwater sleeper (Zhang et al, 2017), triangle sail mussel (Bai et al, 2016), Chinese mitten crab (Qiu et al, 2017), swimming crab (Lv et al, 2017), razor clam (Niu et al, 2017), pikeperch (Guo et al, 2018), and sea urchin (Chang et al, 2018). Previous studies indicated that SLAF-seq, which provides an efficient strategy for large-scale genotyping and high-density genetic map construction, can be generally applicable to various species and populations.…”
Section: Introductionmentioning
confidence: 99%
“…Since the earliest studies utilizing electrophoretic genetic markers on wild populations of molluscs, two of the most commonly observed phenomena have been deficiencies of heterozygous genotypes relative to expectations of Hardy-Weinberg equilibrium (HWE) and deviation from expected Mendelian ratios (segregation distortion) in pair crosses. These phenomena have been observed across the major groups of cultured molluscs and with a variety of marker types, including allozymes (Zouros and Foltz, 1984 ; Mallet et al, 1985 ; Gaffney et al, 1990 ; Beaumont, 1991 ; Toro and Vergara, 1995 ), microsatellites (Bierne et al, 1998 ; Launey and Hedgecock, 2001 ), and SNPs (Peñaloza et al, 2006 ; Vervalle et al, 2013 ; Hedgecock et al, 2015 ; Niu et al, 2017 ). The earliest explanations for these phenomena implicated null alleles, aneuploidy, inbreeding, cryptic population structure (Wahlund effect), or some form of selection (Beaumont, 1991 ).…”
Section: Segregation Distortion and Genetic Loadmentioning
confidence: 99%
“…Similar phenomena have been observed in some fish, suggesting that genes in that particular region have significant pleiotropic effects, controlling a series of related traits. Moreover, the identification of QTLs influencing many traits could enhance genetic progress and molecular marker–assisted breeding and imply that a genetic interaction underlies these traits in aquaculture (Niu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%